2020
DOI: 10.1186/s12888-020-02562-8
|View full text |Cite
|
Sign up to set email alerts
|

The fair decision-making of children and adolescents with high-functioning autism spectrum disorder from the perspective of dual-process theories

Abstract: Background Fairness has received much attention in our society. At present, the findings regarding fair decision-making in high-functioning autism spectrum disorder (HF-ASD) are inconsistent. Previous studies have shown that the fair decision-making of typically developing children is influenced by theory of mind (ToM) and executive functioning (EF). As those with HF-ASD have defects in both domains, this study aims to explore the differences in fair decision-making between children and adolesc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The task represents the conflict between the optimum distribution of rewards (Pareto optimal) and the optimum choice for an individual (Nash equilibrium) ( Apt & Grädel, 2011 ) It is considered an analogue of social interaction and as such it has been used a lot in autism research where social behaviour and interactions are key characteristics of the disorder. Findings concerning the PD task in autism, indicate that, cooperation could improves with age ( Jin et al, 2020 ; Kaartinen et al, 2019 ) and the development of executive functions ( Li, Zhu & Gummerum, 2014 ) and that reputation ( Maurer et al, 2018 ) and the nature of the opponent (actual human or machine) could also influence cooperation. These factors are important for both autistic ( Sally & Hill, 2006 ) and non autistic individuals ( Mienaltowski & Wichman, 2020 ; Milinski & Wedekind, 1998 ; Wang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The task represents the conflict between the optimum distribution of rewards (Pareto optimal) and the optimum choice for an individual (Nash equilibrium) ( Apt & Grädel, 2011 ) It is considered an analogue of social interaction and as such it has been used a lot in autism research where social behaviour and interactions are key characteristics of the disorder. Findings concerning the PD task in autism, indicate that, cooperation could improves with age ( Jin et al, 2020 ; Kaartinen et al, 2019 ) and the development of executive functions ( Li, Zhu & Gummerum, 2014 ) and that reputation ( Maurer et al, 2018 ) and the nature of the opponent (actual human or machine) could also influence cooperation. These factors are important for both autistic ( Sally & Hill, 2006 ) and non autistic individuals ( Mienaltowski & Wichman, 2020 ; Milinski & Wedekind, 1998 ; Wang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, published studies on the neuropsychological functioning of ASD show contrasting results due to methods issued without providing exhaustive answers in explaining the neuropsychological dysfunctions in the ASD population. Studies on social decision-making as cooperation indicated lower correct predictions of others' moves compared with TDCs (81) and an improvement of this ability with age (82,83). Moreover, for individuals with ASD, their cooperation relies on more rigid criteria that does not differ depending on the morality of the interacting partner (84).…”
Section: Discussion and Clinical Implicationsmentioning
confidence: 99%
“…Thus, while these norms may develop differently in autistic children, possibly due to differences in theory of mind (Sally & Hill, 2006), we propose that once these fairness norms are learned and established, they are implemented more consistently when given the chance to share resources in later adolescence and adulthood (Ikuse et al, 2018; Tei et al, 2019). For example, autistic children, but not adolescents, were more likely to accept unfair offers in the ultimatum game (Jin et al, 2020). This view is consistent with findings from other domains in which some autistic individuals use rules as part of compensatory strategies to navigate their social environments (Livingston et al, 2020).…”
Section: Discussionmentioning
confidence: 99%